HEALING COUGHS AND COLDS IN BABIES IN TERMS OF BABY SPA THERAPY AT PMB RIRIN SEVDA KORINI OGAN KOMERING ULU REGENCY 2023 - Muhammad Hasan Azhar; Siska Delvia (Majalah Kedokteran Sriwijaya, 2025)
One of the non-pharmacological therapies used to treat coughs and colds is massage therapy which is currently in great demand by mothers who have toddlers with coughs and colds. This is due to cultural factors, traditions and knowledge about healing diseases. The aim of this research is to determine the cure for coughs and colds in babies in terms of baby spa therapy at PMB Ririn Sevda Korini SKM., S.Keb, Ogan Komering Ulu Regency in 2023. This type of research uses an analytical design with a cross sectional approach, namely research where the independent variable ( Baby Spa) and the dependent variable (curing coughs and colds). The results of the chi-square statistical test showed that the p value was 0.000 (<0.05). This shows that there is a significant relationship between healing coughs and colds and baby spa.